Do South Asian Nutrition Guidelines for Critically Ill Recommend Commercial Feeds or Blended Tube Feeds? – A Narrative Review (Bangladesh Critical Care Journal, 2020)
In the previous years, blended tube feeds have been replaced by commercialized feeds; however, literature suggests that blended tube feeds are still being used to feed critically ill patients. Aim of this narrative review is to review the South Asian Critical Care Nutrition Guidelines type of feed recommendations. From the eight South Asian Countries, Critical Care Nutrition Guidelines are available only from Pakistan, India and Sri Lanka. Review of these guidelines indicate discrepancies with types of feed when compared to international guidelines such as nutrition guidelines from American Society for Parenteral and Enteral Nutrition. Indian and Sri Lankan Guidelines give way to administer Blended Tube Feeds in critically ill patients. There is no available literature to back their recommendation regarding use of blended tube feeds in critically ill patients. Reasons and evidence for recommendations of blended tube feeds need to be explored, while determining whether theses feeds are valid replacement for commercial enteral feeds.Bangladesh Crit Care J March 2020; 8(1): 48-52